Special education as an area for change - Polish and Czech solutions = Edukacja specjalna jako obszar zmian - rozwiązania w Polsce i Czechach - Baczała, Ditta; Zikl, Pavel (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article is devoted to special education interpreted as an area for change. Its purpose is to show the changes that have occurred in the last 30 years and are still occurring in special education in Poland and the Czech Republic. The authors assume that the developments in special education in both countries have taken place thanks to new law and social change in both nations.
Keywords: special education; changes in special education in Poland; changes in special education in the Czech; edukacja specjalna; zmiany w edukacji specjalnej w Polsce; zmiany w edukacji specjalnej w Czechach